Puerarin alleviates inflammation and pathological damage in colitis mice by regulating metabolism and gut microbiota - Zou, Yixin; Ding, Wenjiao; Wu, You; Chen, Tingting; Ruan, Zheng (Frontiers in Microbiology, 2023)
Dysbiosis of gut microbiota and metabolic pathway disorders are closely related to the ulcerative colitis. Through network pharmacology, we found that puerarin is a potential ingredient that can improve the crypt deformation and inflammatory infiltration in mice, and decrease the levels of IL-1β, IL-6 and TNF-α significantly. Listeria, Alistipes and P. copri gradually became dominant bacteria in UC mice, which were positively correlated with inflammatory factors. Puerarin effectively improved dysbiosis by reducing the abundance of Alistipes, P. copri and Veillonella, and increasing the level of Desulfovibrionacea. Correlation network and metabolic function prediction analysis of the microbiota showed that they formed a tightly connected network and were widely involved in carbohydrate metabolism and amino acid metabolism. Specifically, we observed significant changes in the tryptophan metabolism pathway in DSS mice, with an increase in the abundance of Bacteroidetes and Enterobacteriaceae involved in tryptophan metabolism. However, this metabolic disorder was alleviated after puerarin treatment, including the reversal of 3-HAA levels and an increase in the abundance of Rhodobacteraceae and Halomonadaceae involved in kynurenine metabolism, as well as a significant increase in the purine metabolite guanosine. In conclusion, our study suggests that puerarin has a good therapeutic effect on UC, which is partially achieved by restoring the composition and abundance of gut microbiota and their metabolism.